IDNLearn.com: Where your questions meet expert answers and community support. Discover reliable and timely information on any topic from our network of knowledgeable professionals.
Sagot :
Solve for the first variable in one of the equations, then substitute the result into the other equation.
Point Form: (3,4)
Equation Form:
x=3, y=4
Point Form: (3,4)
Equation Form:
x=3, y=4
Answer:
x = 3
y = 4
Step-by-step explanation:
2x + y = 10 -----------------(I)
y = x + 1 ---------------------(II)
Substitute y = x + 1 in equation (I)
2x + x + 1 = 10 {Combine like terms}
3x + 1 = 10 {Subtract 1 from both sides}
3x = 10 -1
3x = 9 {Divide both sides by 3}
x = 9/3
x = 3
Plugin x = 3 in equation (II)
y = 3 + 1
y = 4
We are delighted to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. Your search for solutions ends at IDNLearn.com. Thank you for visiting, and we look forward to helping you again.